‘Touching up, repainting, varnishing or renovating’, 100 years’ restoration history of the paintings (Bulletin KNOB, 2010)
Since 1903 a lot of wall paintings have been discovered in the main church in Breda, on the walls as well as on the pillars and vaults. Detailed attention has been paid to the art-historical aspects of the paintings in various publications. However, the techniques, the materials used and the considerations that led to the choice of a specific approach have hardly been accounted for. The archival documentation (photographs, letters, notes, reports and accounts) at the National Service for Cultural Heritage and the Municipality of Breda, however, provide important although still incomplete information. Even the latest restorations, executed in the nineties of the previous century, were not properly mapped by the parties involved.It seems that in Breda it was not until long after the Reformation that the paintings were whitewashed; the paintings in the Prinsenkapel (Princes’ chapel) not until after 1819. It turned out that the paintings were already damaged and dirty before being whitewashed, and in some cases they had even been restored or touched up before. The whitewashing contributed to the preservation of the paintings to a considerable extent, because the paintings were protected by the whitewash. When in the early twentieth century the paintings emerged, they were once again exposed to negative factors (moist, pollution, and the like). The various restorations, however, have also had a great impact on the preservation of the authenticity of the paintings.When the first paintings were discovered, many of them proved to be in a bad condition. Uncovering them too roughly, the earlier damage to them, but also the damp walls had seriously affected the paintings. Consequently, the restoration of the paintings was started very quickly.These first restorations took approximately thirty years. After these restorations, however, the work was not completed yet and three more periods of large-scale restorations followed, which were to last the entire twentieth century. From the beginning of the restoration activities there was detailed discussion on the restoration method. The discussion was not so much about technical or material questions, but mainly about the degree of touching-up and completing and about the starting point that in principle restoration should consist of mere conservation, without additions and with the utmost limitation of touch-ups. In 1915 the Netherlands Society of Antiquarians (KNOB) formulated as one of its principles: ‘preservation has priority over renovation’.This starting point always served as a guideline in the restorations, although in their execution touching-up or filling up voids nevertheless took place frequently. Restoration is a question of choosing and the choices were often personal and a product of the times. It is striking that from the 1990s onwards there was a growing desire among the church council of the main church to restore the paintings as much as possible to their ‘former glory’. The restorer concurred with this to a large extent.The painting of the Annunciation and the vault paintings of choir and transept are distinct examples of this. After objections from the supervisory committee of the restoration somewhat more reserve was exercised in the restoration of the paintings in the nave.